Energia awangardy, czyli o pewnym przypadku logowizualnego perpetuum mobile - Śniecikowska, Beata (Przestrzenie Teorii, 2024)
The article concerns one of the most obscure and most daring (in terms of graphical experimentation) verbo-visual works of the Polish Great Avant-garde – the booklet Wąż, Orfeusz i Eurydyka [Serpent, Orpheus and Euridice, 1922] by Tytus Czyżewski, a painter and man of letters. The printed drama consists of double-spreads made of drawings (presented on the left pages) and text of a one-act play (always placed on the right). In her analyses Śniecikowska refers to the concept of “niezrozumialstwo” [nonunderstandableness] introduced by the Polish pre-war literary critic, Karol Irzykowski, focusing on the positive aspects of “understanding non-understanding”. She reveals possible similarities between Czyżewski’s artistic practice and the Surrealist technique of automatic drawing. She also uncovers some unclear connections between the visual and the textual within the booklet and points to the relations of Czyżewski’s work and the 21st century experiments with verbo-visuality.